The Emerging Specialty of Oral Medicine (International Journal of Food and Nutritional Sciences, 2022)
Background: Within the field of dental medicine, there is a specialty called oral medicine. This field, which is frequently seen as being at the nexus of medical and dentistry, is now essential to both pre- and postdoctoral dental education. Most of the globe recognises oral medicine as a dental speciality, and it is currently an emerging field. In the past, oral medicine was not clearly defined by a group of experts. Recent research investigations on clinical practise and worldwide postgraduate programmes in oral medicine have contributed to clarify information about oral medicine from a variety of angles. The definition of oral medicine will be examined in this article along with a revised definition based on current research, which will be presented.Dental schools have recently created educational criteria that must be followed in order for the institutions to receive accreditation; some of these standards have a direct connection to oral medicine. [1] Curriculum recommendations have been made for postdoctoral training programmes in oral medicine. [1, 2] Recent requirements for advanced general dentistry and oral medicine have been approved by the Commission on Dental Accreditation (CODA), with which all accredited training institutions must comply. [3]